2019
DOI: 10.3748/wjg.v25.i11.1409
|View full text |Cite
|
Sign up to set email alerts
|

Gluten immunogenic peptide excretion detects dietary transgressions in treated celiac disease patients

Abstract: BACKGROUNDLife-long removal of gluten from the diet is currently the only way to manage celiac disease (CeD). Until now, no objective test has proven useful to objectively detect ingested gluten in clinical practice. Recently, tests that determine consumption of gluten by assessing excretion of gluten immunogenic peptides (GIP) in stool and urine have been developed. Their utility, in comparison with conventional dietary and analytical follow-up strategies, has not been fully established.AIMTo assess the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 28 publications
(48 reference statements)
6
60
1
Order By: Relevance
“…Our findings suggest that symptoms associated with IBS are incorrectly attributed to recent exposure to gluten, even though IBS is common in patients treated for coeliac disease. 21 Our findings also highlight the limitations of symptoms in general as a clear-cut readout of gluten ingestion and, for clinicians, underscore the value of employing sensitive objective measures of gluten exposure, such as gluten immunogenic peptide assays of urine 23 or faeces, 24,25 to correlate symptoms with true episodes of gluten exposure.…”
Section: Discussionmentioning
confidence: 76%
“…Our findings suggest that symptoms associated with IBS are incorrectly attributed to recent exposure to gluten, even though IBS is common in patients treated for coeliac disease. 21 Our findings also highlight the limitations of symptoms in general as a clear-cut readout of gluten ingestion and, for clinicians, underscore the value of employing sensitive objective measures of gluten exposure, such as gluten immunogenic peptide assays of urine 23 or faeces, 24,25 to correlate symptoms with true episodes of gluten exposure.…”
Section: Discussionmentioning
confidence: 76%
“…The use of faecal and urine gluten immunogenic peptides (GIPs) may provide a practical non-invasive future approach to monitor for gluten exposure in individuals. In a recent study, patients with CD who reported adherence to a strict GFD had a positive GIP, despite the majority of these individuals being asymptomatic [37]. This highlights the potential utility of using GIPs in assessing ongoing gluten exposure.…”
Section: Dietary Indiscretionmentioning
confidence: 99%
“…Although still modest in size, this is the largest published study on the influence of a GFD instituted shortly after T1D onset. To our knowledge, we are the only researchers to assess adherence to GFD intervention using laboratory stool tests for gluten antigens . We also administered QoL questionnaires at the end of the intervention to assess whether a GFD is associated with an additional psychological burden.…”
Section: Discussionmentioning
confidence: 99%